Serum alkaline phosphatase/creatinine ratio serving as a screening tool for low lumbar bone mineral density in patients with degenerative lumbar scoliosis - Zhenning Cai; Xing Sun; Bo Shi; Zhenhua Feng; Sen Li; Zezhang Zhu; Yong Qiu; Benlong Shi (Journal of Orthopaedic Surgery and Research)
Abstract Purpose (1) To figure out a simple and effective indicator that could assist in the assessment of bone mineral density (BMD) based on big data and (2) to verify its predictive value for low BMD among patients with degenerative lumbar scoliosis (DLS). Methods A total of 6,167 participants from the National Health and Nutrition Examination Survey (NHANES) database (2009–2010, 2013–2014, 2017–2018) and 166 patients who were diagnosed with DLS and hospitalized in our center between June 2019 and April 2023 were enrolled in the study. Cases were divided into two groups based on whether the T-score was below − 1. The Osteopenia Index (OI) was defined as the ratio of alkaline phosphatase (ALP) (IU/L) to creatinine (mg/dL). Multivariable logistic regression was performed to identify risk factors, while restricted cubic spline (RCS) analysis was applied to explore the potential non-linear relationship. Patients with DLS from our center were used to validate the diagnostic value of OI through receiver operating characteristic curve (ROC) analysis. Results Participants from NHANES were divided into three subgroups according to the tertiles of OI: subgroup 1 (OI < 68), subgroup 2 (68 ≤ OI < 93), and subgroup 3 (OI ≥ 93). A multivariable logistic regression model adjusted for age, gender, and race revealed that elevated OI was a significant risk factor for osteopenia (subgroup 2 vs. subgroup 1: odds ratio [OR] = 1.473, 95% confidence interval [CI] = 1.173–1.849; subgroup 3 vs. subgroup 1: OR = 2.092, 95% CI = 1.566–2.796). Moreover, the RCS plot showed that the risk of osteopenia gradually increased with the elevation of OI. In patients with DLS, OI showed a significant correlation with lumbar T-score (ρ = − 0.392) and HU value (ρ = − 0.373) (both P < 0.001). ROC analysis revealed that the area under the curve of OI was 0.757, and the cut-off value was set at 124.73 according to the Youden index. A nomogram based on a logistic regression model adjusted for age, gender, and blood urea nitrogen was plotted, with a McFadden R² of 0.212. Conclusion OI correlated significantly with lumbar BMD and HU value. Logistic regression and RCS analysis demonstrated that OI could serve as a simple, economical, and effective screening tool for low lumbar BMD in DLS patients, with its predictive ability further enhanced when adjusted for age and gender.